CipA mediates complement resistance of Acinetobacter baumannii by formation of a factor I-dependent quadripartite assemblage - Ries, Julia I.; Heß, Marie; Nouri, Noura; Wichelhaus, Thomas A.; Göttig, Stephan; Falcone, Franco H.; Kraiczy, Peter (Frontiers in Immunology, 2022)
Multidrug-resistant Acinetobacter baumannii is known to be one of the leading pathogens that cause severe nosocomial infections. To overcome eradication by the innate immune system during infection, A. baumannii developed a number of immune evasion strategies. Previously, we identified CipA as a plasminogen-binding and complement-inhibitory protein. Here we show that CipA inhibits all three complement activation pathways and interacts with key complement components C3, C3b, C4b, C5, Factor B, Factor D, and in particular Factor I. CipA also targets function of the C5 convertase as cleavage of C5 was impaired. Systematic screening of CipA variants identified two separate binding sites for C3b and a Factor I-interacting domain located at the C-terminus. Structure predictions using AlphaFold2 and binding analyses employing CipA variants lacking Factor I-binding capability confirmed that the orientation of the C-terminal domain is essential for the interaction with Factor I. Hence, our analyses point to a novel Factor I-dependent mechanisms of complement inactivation mediated by CipA of A. baumannii. Recrutiment of Factor I by CipA initiates the assembly of a quadripartite complex following binding of either Factor H or C4b-binding protein to degrade C3b and C4b, respectively. Loss of Factor I binding in a CipA-deficient strain, or a strain producing a CipA variant lacking Factor I-binding capability, correlated with a higher susceptibility to human serum, indicating that recruitment of Factor I enables A. baumannii to resist complement-mediated killing.